SIGNIFICANCE OF CYTOMEGALOVIRUS INFECTION IN CHILDREN WITH CHRONIC TONSILLITIS (ResearchJet Journal of Analysis and Inventions, 2023)
Very often, the inflammatory pathology of the ENT organs leads to chronicity of the process, especially if the process is localized in the tonsils. The chronic inflammatory process in the tonsils has its own characteristics, in particular, the process is characterized by stages of development, as well as in the close relationship of normal and pathological processes. The basis for this study was the high frequency of occurrence and significance of CMVI in children.